Exploring FinTech Lending: The Influence of Financing and Economic Factors on the Success of Peer-to-Peer (P2P) Funded Loans - Ramdhan, Nur’Asyiqin; Bujang, Imbarine; Muhamat, Amirul Afif (Information Management and Business Review, 2023)
This research intends to integrate financing and economic factors into a unified model to explore their influence on P2P lending successful fundraising. An innovative framework of the ARDL method was utilized to explore the short and long-term effects of the factors model to allow the P2P lending players to make informed decisions and develop effective strategies for sustainable FinTech lending practices. Information asymmetry is a persistent concern, and the quality of information provided by both internal and external sources plays a crucial role in determining lender decisions. It aims to offer a holistic understanding of how these elements interact and collectively influence P2P lending loan success, emphasizing the importance of transparency and efficient online lending practices.